Aspects of International Fragmentation - Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2002)
The paper uses a specific-factors framework to address efficiency and distributional implications of international fragmentation which is driven by a foreign location advantage due to a low wage rate. Focusing on the cost-savings linkage between fragmentation and labor demand in the remaining domestic activities, I establish a fragmentation surplus which is familiar to the immigration surplus. However, if the capital which is specific to the fragment produced abroad is an indivisible asset, then fragmentation may cause a domestic welfare loss, because outsourcing takes place in discrete steps where it affords firms quasi-market-power on the domestic labor market. The regime shift from purely domestic production to fragmentation is modeled as a two-stage game. In the first stage firms locate their indivisible assets at home or abroad, and in the second they choose optimal employment. The share of fragmented firms is endogenously determined. The paper explores the conditions determining whether the process of fragmentation caused by less costly outsourcing is beneficial for the domestic economy.
Keywords: 330; Globalisierung; Outsourcing; Spieltheorie